INTEGRATING ARTIFICIAL AND HUMAN INTELLIGENCE THROUGH AGENT ORIENTED SYSTEMS DESIGN - Miller, Michael E. (CRC PRESS, 2024)
This book departs from the assumption that Artificial Intelligence (AI) systems will provide a maximum advantage by replacing human cognitive processing. Instead, this book subscribes to the assumption that AI systems will provide a maximal advantage when the system is specifically designed to augment human intelligence. It provides methods for designing effective systems that include one or more humans and one or more AI entities and uses the approach that assumes automation does not replace human activity but fundamentally changes the structure of human work when AI is added to existing systems. Integrating Artificial and Human Intelligence through Agent Oriented Systems Design discusses the potential impact of AI on human work and life and explores why teamwork is necessary today for complex work environments. The book explains the processes and methods humans employ to effectively team with one another and presents the elements of artificial agents that permit them to function as team members in joint human and artificial teams. It discusses design goals and illustrates how the methods that have been used to model the complex interactions among human and artificial agents can be expanded to enable the design of interaction between them to make possible the attainment of the shared goals. Model-Based Systems Engineering (MBSE) tools that provide logical designs of human-agent teams, the AI within these teams, training to be deployed for human and artificial agent team members, and the interfaces between human and artificial agent team members are all covered. MBSE files containing profiles and examples for building MBSE models used in the design approach are featured on the author's website (https://lodesterresci.com/hat). This book is an ideal read for students, professors, engineers, and project managers associated with designing and developing AI systems or systems that seek to incorporate AI.
Keywords: Artificial intelligence; Intelligence artificielle; artificial intelligence; COMPUTERS / Artificial Intelligence